ДАЙКИ БАЗИТОВ ОСТРОВА ПОНЬГОМ-НАВОЛОК (БЕЛОМОРСКО-ЛАПЛАНДСКИЙ ПОЯС) - Байкова В.С.; Богомолов Е.С.; Зингер Т.Ф. (My University, 2005)
There are four generations of mafic (basic) dikes intruding plutons of the Late Archean enderbites (first and second generations), the Early Proterozoic granodiorites (third generation) and the Late Proterozoic blastomylo-nites developed over both those plutons (the fourth one). Dikes of the first and fourth generations are composed of basalts, second and third ones - of andesite-basalts. Degree of their metamorphism varies from the granulite facies (I and II) down to high- (III) and low-temperature (IV) stages of amphibolite facies. All these dikes are characterized by the weakly fractional distribution of REE, but the degree of this fractionation increases up for 108 the later dikes. Thus, the (La/Yb)N ratio changes, from the first generation to the fourth one, as following: (1.78-2.04) → 6.17 → 5.17 → (4.33-4.22). The higher contents of V, Ti, Y and HREE, and the lower ones of LREE, Ba, Rb, Sr, Cr and Ni, in the first generation dikes, as related to the later ones, are considered as an evi-dence of heterogeneity of a mantle protolith in the dike-forming melting spot. The (Sm/Nd)N ratio decreases from the first generation dikes (0.84-0.91) down to second (0.69) and the third (0.68) ones, but weakly increa-ses in the fourth generation (0.70-0.71). It may be interpreted by some displacement of the melting spots up to the higher levels, or contamination of the mantle-originated melts by the crust substance. Data of Sm-Nd isotope analysis support the formation of dike-forming melt from the mantle sources and mark off some its contaminati-on by the crust substance: the minimum one for dikes of the first generation and the maximum one for the second ones. Comparison of contents of REE and trace elements and their indicator ratios in dikes and the plutons make some base for conclusion about independence and different depths of their melt-forming spots.
Keywords: [551.3:551.71/72+546.65](470.22)